PSYCHOLOGİCAL ASPECTS OF THE DEVELOPMENT OF ACADEMİC ACHİEVEMENT İN STUDENTS - Gahramanli, Nilufer (Revista Gênero e Interdisciplinaridade, 2025)
The study is devoted to the study of the psychological mechanisms of the development of academic achievement. The results of the study showed that there is a positive relationship between the expression of search behavior and self-sufficiency, self-esteem and a sense of ownership and effectiveness of the individual. This relationship can be explained, on the one hand, by the fact that search behavior occurs in conditions of uncertainty and requires serious efforts. Therefore, it requires the beginning of self-confidence and high self-esteem. On the other hand, maintaining the adequacy of activity in difficult situations and not being inclined to give up allows you to increase self-esteem. The study showed that students with low cognitive-search activity and, accordingly, low self-esteem, when faced with unsuccessful situations in the search, more often give up the search or give up. Unfortunately, a situation often arises when receiving negative assessments in educational activities, which can follow one after another. At the same time, such a situation not only discourages the student from intensive knowledge acquisition, but also undermines confidence in their resources, capabilities and hope for optimization of their positions, weakens cognitive interest in professional activity. As a result, learned helplessness can develop quite quickly. This category of students is more susceptible to disappointment from failures in educational and professional activities. These students do not try to identify the reasons and draw conclusions and are inclined to abandon educational activities. These facts should be taken into account.